Pemberdayaan Masyarakat Dalam Pemanfaatan Material Lokal Guna Pengembangan Ekowisata Berbasis Local Wisdom Desa Sidem - Saputri, Diyah Ayu; Junianto, Mochamad Rizqy (Jurnal Pengabdian Masyarakat Bhinneka, 2022)
Local wisdom is the capital of the formation of noble characters who live in society, grow and develop continuously in public awareness. Local wisdom can be in the form of local knowledge, local skills, local intelligence, local resources, local social processes, local norms and ethics and local customs. Likewise in the field of architecture, local wisdom is an architectural design that adapts to the local climate, using local techniques and materials that are influenced by social, cultural and economic aspects of the local community. In this case, the selected location where the concept of local wisdom will be implemented is in Sidem Village, Gondang District. The purpose of this community service is to empower the community in the use of local materials for the development of Ecotourism based on Local Wisdom in Sidem Village, Gondang Tulungagung District. The implementation techniques used to implement these local local materials are as follows: 1) Preparation Phase. This stage includes team preparation, site survey, interviews with local communities, identification of problems and potentials, analysis of problems and potentials. 2) Implementation Phase. This stage includes the preparation of the draft design, implementation. 3) Evaluation and Reporting Stage. This stage includes evaluation of activities, preparation of activity reports. The result of this service is the implementation of community empowerment socialization by bringing up design concepts, because the community plays an important role in the development of ecotourism in Sidem Village. Keywords - ecotourism, local materials, local wisdom, stakeholders, Tulungagung